2019
DOI: 10.1088/1361-6463/ab50a1
|View full text |Cite
|
Sign up to set email alerts
|

A 2D ZnSe/BiOX vertical heterostructure as a promising photocatalyst for water splitting: a first-principles study

Abstract: A vertical heterostructure is an effective method for regulating the properties of 2D materials that are superior to their individual components due to the interfacial interaction. Here, 2D ZnSe/BiOX (X  =  Cl, Br, I) vertical heterostructures as potential photocatalysts for water splitting are systematically investigated using first-principles calculations. The results indicate that the binding strength of the heterostructure is larger than  −17.6 meV Å−2, favoring its experimental realization. Furthermore, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 75 publications
0
8
0
Order By: Relevance
“…[34] Because heterostructure can not only preserve the property of its individual component, but also introduce advanced functional. [35][36][37] For example, the heterostructure of the different semiconductors could exhibit unusual band gap. [38,39] What's more, intrinsic electric filed may generally exist in the heterostructure, and it would help to separate the carriers.…”
Section: Introductionmentioning
confidence: 99%
“…[34] Because heterostructure can not only preserve the property of its individual component, but also introduce advanced functional. [35][36][37] For example, the heterostructure of the different semiconductors could exhibit unusual band gap. [38,39] What's more, intrinsic electric filed may generally exist in the heterostructure, and it would help to separate the carriers.…”
Section: Introductionmentioning
confidence: 99%
“…But for Janus ones (Figure d–f), there is a great potential drop (1.096, 5.658, and 6.801 eV for Zr 2 N 2 ClBr, Zr 2 N 2 ClI, and Zr 2 N 2 BrI, respectively) between different X atoms layers, which induces a strong electrostatic field to be formed between the layers with transport barriers, implying that electrons are transferred between different X atoms layers . More importantly, the great potential drops have positive significance for low recombination rate and electrostatic potential difference (ΔΦ), which induce intrinsic dipoles to generate a built-in electric field, which is beneficial to the separation of photoinduced electron–hole pairs, improving the performance of (photo)­electric devices. , …”
Section: Resultsmentioning
confidence: 99%
“…25 Another such attempt involving ZnSe is the ZnSe/BiOX vertical heterostructure as a promising photocatalyst for water splitting under visible light using first-principles study. 26 Hussain et al have recently used hybrid density functional theory to study the optoelectronic properties of ZnSe 1Àx Te x for photocatalytic applications. 27 They have found that for x = 0.25 and 0.5, the charge carrier separation can be improved and these solid solutions are promising for the photocatalytic reduction of CO 2 and oxidation of water.…”
Section: Introductionmentioning
confidence: 99%
“…25 Another such attempt involving ZnSe is the ZnSe/BiOX vertical heterostructure as a promising photocatalyst for water splitting under visible light using first-principles study. 26 Hussain et al . have recently used hybrid density functional theory to study the optoelectronic properties of ZnSe 1− x Te x for photocatalytic applications.…”
Section: Introductionmentioning
confidence: 99%